2021
DOI: 10.26434/chemrxiv-2021-3bllg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-⍺/β Polymorphism of PSMα3 Fibrils

Abstract: The formation of ordered cross-β amyloid protein aggregates is associated with a variety of human disorders. While conventional infrared methods serve as sensitive reporters of the presence of these amyloids, the recently discovered amyloid secondary structure of cross- fibrils presents new questions and challenges. Herein, we report results using Fourier Transform infrared (FTIR) spectroscopy and two-dimensional infrared (2DIR) spectroscopy, to monitor the aggregation of one such cross-alpha forming peptide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…27 The presence of a b-sheet component was also observed in the case of cross-a peptides such as PSMa3. 36 The percentage area of this subband clearly distinguishes coiled-coil oligomers from fibrils. The presence of both amide features arising from helical and intermolecular aggregates confirmed that a,b-peptide structures can form fibrils.…”
Section: Secondary Structure Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The presence of a b-sheet component was also observed in the case of cross-a peptides such as PSMa3. 36 The percentage area of this subband clearly distinguishes coiled-coil oligomers from fibrils. The presence of both amide features arising from helical and intermolecular aggregates confirmed that a,b-peptide structures can form fibrils.…”
Section: Secondary Structure Evaluationmentioning
confidence: 99%
“…Interestingly, not all stained structures exhibit birefringence under polarized light, which is characteristic of amyloids in tissues. 36,44 For peptides 1_b and 2_b, it was difficult to observe formed structures, presumably because shorter fibrils (a few mm long) may not be visible at the 200Â magnification during imaging. 45 All the bright structures seen in the background of the samples that do not resemble fibrils are likely to be smaller structures that bind to CR dye.…”
Section: Nanostructure Studiesmentioning
confidence: 99%